Risk Mitigation of National Amil Zakat Agency Tanah Datar Regency - Sari, Chitra Indah; Rizal, Rizal; Nurhamima, Nurhamima (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study examines the integration of ISO 31000 into risk management practices at the National Amil Zakat Agency (BAZNAS) in Tanah Datar Regency. A qualitative field research methodology was employed, involving in-depth interviews with key informants. Data triangulation ensured the validity of the findings, while thematic analysis identified core patterns and themes. The theoretical framework utilized ISO 31000's risk management process, including risk identification, analysis, and treatment. The findings revealed ten significant risks categorized into financial, operational, strategic, and hazard risks. High-priority risks include the absence of sanctions for non-compliant zakat payers, while medium-level risks involve the failure to meet zakat targets and inaccuracies in beneficiary selection. Low-priority risks include errors in recommending zakat recipients by local officials. The integration of ISO 31000 provides a systematic approach to identifying and mitigating these risks, ensuring more transparent and accountable zakat management. The study offers actionable recommendations for BAZNAS, including strengthening public education on zakat, implementing stricter verification processes for beneficiaries, and fostering community-based approaches to encourage zakat payments